Adsorption of nitrate by biochar prepared from rice husks (o. Sativa l., om5451) - Phương, Nguyễn Đạt; Phượng, Đỗ Thị Mỹ; Chiếm, Nguyễn Hữu; Thoa, Phạm Ngọc; Lộc, Nguyễn Xuân (Hue University Journal of Science: Natural Science, 2021)
This study assesses the influence of solution pH, biochar dose, reaction time, and initial nitrate concentration on the nitrate adsorption in aqueous solutions by biochar prepared from rice husks (O. sativa L., OM5451). The biochar was prepared with the pyrolysis method at 700 °C. The pHpzc of the biochar is 9.51. The optimal conditions for the adsorption process include biochar 0.5 g, pH = 4, time 120 minutes, and initial concentration of 50 . Under the optimal conditions, the nitrate removal efficiency is 69.7%. The adsorption equilibrium data are more consistent with the Langmuir isothermal model ( = 0.993) than the Freundlich isothermal model ( = 0.965), and the maximal nitrate adsorption capacity of the biochar, calculated from the Langmuir equation, is 12.843 mg·g–1. The adsorption of the biochar fits well with both the pseudo-first-order kinetic model ( = 0.964) and the pseudo-second-order kinetic model ( = 0.963).